Andras Nursing Informatic System Application (Annisa) dalam Upaya Meningkatkan Pengetahuan Perawat tentang Dokumentasi Keperawatan - Candra Saputra; Yulastri Arif; Fitra Yeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the effectiveness of ANNISA development on nurses' knowledge of nursing documentation. This method uses quantitative research with a quasi-experimental design and a time series approach non-equivocal control group design. The study results were there were differences in the measurement of nurses' knowledge about nursing documentation in the intervention group before the intervention by measuring posttest-1 with p-value = 0.000. There were differences in nurses' experience about nursing documentation between the intervention group and the control group in the posttest-1 and posttest-2 measurements after the intervention using ANNISA with p-value = 0,000. There was an increase in differences in nurses' knowledge about nursing documentation from the pretest, posttest-1, and posttest-2 measurements after using ANNISA in the intervention group and the control group with p-value = 0.000. In conclusion, ANNISA development affects increasing the knowledge of nurses about nursing documentation Keywords: ANNISA, Nursing Documentation, Knowledge